2008
DOI: 10.4337/9781848442702
|View full text |Cite
|
Sign up to set email alerts
|

Handbook of Organizational Routines

Abstract: Reconceptualizing organizational routines as a source of flexibility and change Tools for inventing organizations: Toward a handbook of organizational. Notwithstanding first efforts to understand interorganizational routines, it is still un-In M. C. Becker (Ed.), Handbook of organizational routines: 228-255.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
21

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 0 publications
2
60
0
21
Order By: Relevance
“…Desta forma, capacidades e seus valores são fenômenos construídos socialmente, consumindo tempo, adicionando e rearranjando conexões entre os componentes. Assim, deve-se repensar os aspectos culturais e de hábito dos envolvidos de forma a promover o efetivo desenvolvimento das rotinas da capacidade (Amit & Schoemaker, 1993;Becker, 2008;Bingham et al, 2007;Bitar & Hafsi, 2007;Helfat & Peteraf, 2003;Kogut & Zander, 1992;Nelson & Winter, 1982;Pandža et al, 2003;Sanchez & Heene, 1997;Stevens, 1998) …”
Section: Componentes De Capacidades Organizacionais E Combinaçãounclassified
“…Desta forma, capacidades e seus valores são fenômenos construídos socialmente, consumindo tempo, adicionando e rearranjando conexões entre os componentes. Assim, deve-se repensar os aspectos culturais e de hábito dos envolvidos de forma a promover o efetivo desenvolvimento das rotinas da capacidade (Amit & Schoemaker, 1993;Becker, 2008;Bingham et al, 2007;Bitar & Hafsi, 2007;Helfat & Peteraf, 2003;Kogut & Zander, 1992;Nelson & Winter, 1982;Pandža et al, 2003;Sanchez & Heene, 1997;Stevens, 1998) …”
Section: Componentes De Capacidades Organizacionais E Combinaçãounclassified
“…Agents therein have limited memories and cognitive capacities and assume that the rationality of others is similarly bounded (Hodgson 2007b). The work of Nelson and Winter (1982) has already generated extensive discussion of the role of routines in storing information within organisations (Becker 2008). More broadly, generalised Darwinian principles point to the need to examine different mechanisms of information retention and transmission between institutions, and the conditions of informational replication that have the potential to generate greater complexity (Hodgson and Knudsen, in press).…”
Section: Metcalfe (P 36) Continuesmentioning
confidence: 99%
“…Many people find it more productive to keep using an old, familiar technology than rapidly adapt to a new technology." Becker (2008) [2] suggested a possible function of organizational routines as a part of the family of concepts such as institutions, norms or conventions that can be the source of both stability and change. Davis (2009) [9] identified that the highly dynamic environments require flexibility to cope with a M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%